Analysis of the Romanian beef market - Irina-Adriana Chiurciu; Elena Cofas (Agrarian Economy and Rural Development - Realities and Perspectives for Romania. International Symposium. 12th Edition, 2021)
The paper presents the existing situation on the beef market in Romania, compared to the situation encountered in the European Union and implicitly the position that our country occupies in this regard. The study was conducted for the period 2015-2020 and reflects the fact that Romania is not among the main cattle breeders and beef producers in the European Union. Moreover, there were registered decreases for the analyzed period for most of the indicators studied: for the number of cattle the decrease was 8.67%, slaughtered cattle - 36.64%, beef production - 27.61%, and in the category of cattle meat value exports - over 30%. Indicators fow which increases in values were observed: average purchase prices for live animals, for most Development Regions, and imports of fresh or chilled beef.
Keywords: Q10; 330; beef production; bovine effectives; bovines slaughtered; exports; imports